Swedish Lawyers’ Studies Abroad During the Seventeenth Century: A Mix of State-Building Process and Personal Ambitions - Marianne Vasara-Aaltonen (Clio@Themis, 2022)
This article delves into the studies abroad of Swedish lawyers during the seventeenth century. It discusses what universities were especially popular and at what times, the social backgrounds of the students and their career paths. Studying abroad was connected to the ongoing state-building process in Sweden as well as to the personal ambitions of the students. Furthermore, the connection between studying abroad and the development of the Swedish legal profession, as well as how studies abroad contributed to the reception of foreign law, are discussed.